2014
DOI: 10.1016/j.socscimed.2014.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma and metabolic syndrome in men and women

Abstract: The long-term effects of childhood trauma on health are well-documented, but few population-based studies have explored how childhood trauma affects the risk of developing metabolic syndrome (MetS) in adulthood. Using data from 1,234 adults in the second wave of the Midlife Development in the U.S. survey (2004), we investigate (1) the extent to which childhood abuse affects the risk of developing MetS in adulthood; (2) how the severity of different types of abuse (emotional, physical, sexual, or cumulative abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
84
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 60 publications
9
84
2
1
Order By: Relevance
“…Over the past 20 years, several studies have investigated the association between chronic stress and prevalent or incident metabolic syndrome (Bergmann et al, 2014;Di Castelnuovo et al, 2013;Fabre et al, 2013;Frisman & Kristenson, 2009;Goldbacher & Matthews, 2007;Hjemdahl, 2002;Horri et al, 2010;Lee et al, 2014;Puustinen et al, 2011;Pyykkonen et al, 2010;Raikkonen et al, 2007;Troxel et al, 2005;Vitaliano et al, 2002;Vogelzangs et al, 2007;Whisman & Uebelacker, 2012;Yamamoto et al, 2011). A recent meta-analysis of the only four prospective studies (Bergmann et al, 2014) that used objective stress measurements, showed that persons who experienced stressful life events had an on average two times higher probability of developing the metabolic syndrome at follow-up (Lee et al, 2014;Raikkonen et al, 2007;Troxel et al, 2005;Vitaliano et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 20 years, several studies have investigated the association between chronic stress and prevalent or incident metabolic syndrome (Bergmann et al, 2014;Di Castelnuovo et al, 2013;Fabre et al, 2013;Frisman & Kristenson, 2009;Goldbacher & Matthews, 2007;Hjemdahl, 2002;Horri et al, 2010;Lee et al, 2014;Puustinen et al, 2011;Pyykkonen et al, 2010;Raikkonen et al, 2007;Troxel et al, 2005;Vitaliano et al, 2002;Vogelzangs et al, 2007;Whisman & Uebelacker, 2012;Yamamoto et al, 2011). A recent meta-analysis of the only four prospective studies (Bergmann et al, 2014) that used objective stress measurements, showed that persons who experienced stressful life events had an on average two times higher probability of developing the metabolic syndrome at follow-up (Lee et al, 2014;Raikkonen et al, 2007;Troxel et al, 2005;Vitaliano et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis of the only four prospective studies (Bergmann et al, 2014) that used objective stress measurements, showed that persons who experienced stressful life events had an on average two times higher probability of developing the metabolic syndrome at follow-up (Lee et al, 2014;Raikkonen et al, 2007;Troxel et al, 2005;Vitaliano et al, 2002). However, these four studies have important methodological limitations: one study only involved 152 participants (Vitaliano et al, 2002), two recruited solely women or men (Raikkonen et al, 2007;Troxel et al, 2005) and one only studied early life events (Lee et al, 2014). Given these limitations, the aim of our current study was to evaluate whether the number of stressful life events is associated with incident metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…However, this study was examining the relationship of childhood adversity in an adult population sample instead of a mood disorders sample. In another population sample study, it was also found that individuals who experienced more cumulative abuse were at greater risk for developing metabolic syndrome (Lee et al, 2014). This difference in findings may be explained in the limitation of our small sample size that may lead to lower power to detect findings.…”
Section: Previous Literaturementioning
confidence: 80%
“…Childhood adversity has been associated with metabolic syndrome and its components, in both community (Danese et al, 2009;Lee, Tsenkova, & Carr, 2014;Riley, Wright, Jun, Hibert, & Rich-Edwards, 2010) and clinical populations (Post et al, 2013). In the 2005 CCHS, childhood physical abuse was associated with obesity in the Canadian population (Fuller-Thomson, Sinclair, & Brennenstuhl, 2013).…”
Section: Childhood Adversitymentioning
confidence: 99%
See 1 more Smart Citation